CULTURAL ARTIFACTS AND THE NARRATIVE OF HISTORY: W. E. B. DU BOIS AND THE EXHIBITING OF CULTURE AT THE 1900 PARIS EXPOSITION UNIVERSELLE - Fisher, Rebecka Rutledge (Modern fiction studies)
The 1900 Paris Exposition Universelle in Paris became the world stage on which W. E. B. du Bois used European and American sociological methods not only to call such narratives into question, but also to construct and popularize the autonomous and self-generated epistemological development of African-American culture. Here, Fisher argues that the exhibition of photographs, books, and data presented by du Bois at the Paris Exposition represented both a literal and a figurative intervention of African Americans into the narratives of European sociology and histography.